Pendampingan Pengembangan Jurnal OJS pada Perguruan Tinggi Keagamaan Islam Swasta di Kalimantan Timur - Sugiyono, Sugiyono; Sumarno, Sumarno; Zaafarani, Hafiz Izzan; Yusuf, Iskandar (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Balikpapan Islamic College is a private Islamic Religious College (PTKI) in Balikpapan, a buffer zone for the IKN (Indonesian Capital City). As an Islamic educational institution, this campus plays a central role in the development of Islam in East Kalimantan through the Tridharma of Higher Education. However, its contribution to the development of publications and scientific works remains largely untouched, including the lack of journal publication facilities that facilitate the need for scientific publications for the community. One contributing factor is limited human resources, therefore assistance is needed in managing scientific publications through the development of the OJS journal. This activity uses the Participatory Action Research (PAR) method, through stakeholder involvement from the planning stage to journal management. Data were collected through observation, interviews, and documentation, then analyzed qualitatively to assess the effectiveness of the program. The results of the community service show that mentoring activities can improve the understanding and skills of independent journal managers. The obstacle faced is limited technical support.